The world's largest hummingbird was described 131 years ago - Areta, Juan Ignacio (2024)
A recent paper in the Proceedings of the National Academy of Sciences USA argued that Giant Hummingbird Patagona gigas comprises two species (‘northern’ and ‘southern’) that differ in morphology, migratory behaviour and, especially, genetics. This proposal merits close consideration, but the introduction of a new name, ‘P. chaski’, for the northern population is unwarranted, as the taxon concerned had already been described, as Patagona peruviana Boucard, 1893. Failure by the authors of ‘P. chaski’ to identify and check the syntypes of P. peruviana, which unambiguously correspond to the same morphotype and taxon as ‘P. chaski’, resulted in the unnecessary erection of a ‘new species’ described already more than a century ago. Here we stabilise nomenclature by designating a lectotype for P. peruviana of which ‘P. chaski’ is a junior synonym.